Disease Progression of Idiopathic Cervical Dystonia in Spite of Improvement After Botulinum Toxin Therapy - Hefter, Harald; Schomaecker, Isabelle; Schomaecker, Max; Samadzadeh, Sara (Frontiers in Neurology, 2020)
Aim of the study: was to demonstrate general progression of symptoms in cervical dystonia (CD) on the one hand and improvement of some special symptoms on the other hand after botulinum toxin (BoNT) therapy. Methods: 74 patients with idiopathic CD under continuous treatment in a botulinum toxin outpatient department with at least three injections, completed a short questionnaire. They were asked whether pain, increased muscle tone and tension, reduced mobility of the head, abnormal head position, head tremor, or other symptoms had been present at the onset of BoNT-therapy and which symptoms were present at the time of recruitment. Patients had to rate actual severity of CD in percent of the severity of CD at the onset of BoNT-therapy. The TSUI score was determined by the treating physician. Blood samples were taken to analyze induction of neutralizing antibodies. Results: Mean improvement of CD reported by the patients and scored by the physician was about 50%. The frequency of all symptoms increased with duration of therapy. The symptom most frequently improved was abnormal head position. The longer the time span between onset of symptoms and onset of BoNT-therapy was, the higher was the actual TSUI score and the lower the improvement reported. Twelve patients had positive antibody tests. Conclusions: Patients experience a progression of CD, but recognize improvement of abnormal head position due to BoNT-therapy. The longer patients have been without BoNT- therapy, the poorer is the long-term outcome independent on duration of BoNT treatment. Therefore BoNT-therapy should be initiated as early as possible.